Husbands & lovers : a novel [large type] - Williams, Beatriz (Random House Large Print, 2024)
"Connecticut, 2022. Mallory Dunne has spent her life trying to be a good mother to her son, Sam. Raising him alone is hard, even with the help of her sister. Two years ago, Sam ingested a toxic mushroom and fell into a coma. Now recovered, he needs a new kidney to live a normal life, forcing Mallory to track down his father in the hope that they're a match. Her journey to find him again transports her back to the summer they spent on the paradise of Winthrop Island - a time of music, porch cocktails, young love, and the site of a terrible event that drove Mallory from his arms. Cairo, 1951. Hannah Ainsworth cannot escape the war that destroyed her life, her first love - and her hope for a brighter future. A Hungarian émigré married to a hapless Britishman working for the Foreign Office, Hannah is thrown into the parched but bustling desert landscape of Egypt, now convulsing with revolution. Looking for passion, she begins a dangerous affair with an enigmatic hotel manager who shows her the majesty of the pyramids and his nation. But their newfound romance has perilous consequences, and Hannah must decide how much she's willing to risk for the pursuit of love. Mallory's moving journey to protect her son intertwines with Hannah's explosive affair in surprising, illuminating ways. Husbands & Lovers is the epic story of two fierce women united by an heirloom, passed down to Mallory by her own mother - a cobra bracelet with a mysterious provenance, studded with gems and secrets"--